2015
DOI: 10.1016/j.molcel.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Distinct tRNA Accommodation Intermediates Observed on the Ribosome with the Antibiotics Hygromycin A and A201A

Abstract: SUMMARY The increase in multi-drug resistant bacteria is limiting the effectiveness of currently approved antibiotics, leading to a renewed interest in antibiotics with distinct chemical scaffolds. We have solved the structures of the Thermus thermophilus 70S ribosome with A-, P- and E-site tRNAs bound, and in complex with either the aminocyclitol-containing antibiotic hygromycin A (HygA) or the nucleoside antibiotic A201A. Both antibiotics bind at the peptidyl transferase center and sterically occlude the CCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
117
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(130 citation statements)
references
References 71 publications
12
117
1
Order By: Relevance
“…Ribosomes were concentrated to ∼5 mg/mL. In vitro-coupled transcription-translation assays were carried out as described previously using purified components (27).…”
Section: Methodsmentioning
confidence: 99%
“…Ribosomes were concentrated to ∼5 mg/mL. In vitro-coupled transcription-translation assays were carried out as described previously using purified components (27).…”
Section: Methodsmentioning
confidence: 99%
“…Computational3536 and experimental283738 studies have implicated the following sequence of conformational rearrangements during aa-tRNA accommodation: (1) aa-tRNA moves from an A/T to an elbow-accommodated (EA) conformation, (2) the aa-tRNA arm accommodates into the A-site and (3) the 3′-CCA end enters the peptidyl transferase centre (PTC). The first simulations of factor-free accommodation employed targeting techniques and showed that sequential movement of the elbow, arm and 3′-CCA end is sterically accessible35.…”
mentioning
confidence: 99%
“…4 Its chemical structure includes a moiety derived from D-rhamnose, the N 6 , N 6 -dimethyl-3ʹ-amino-3ʹ-deoxyadenosyl (aminonucleoside) moiety of puromycin, an α-methyl-p-coumaric acid (a polyketide) and an unsaturated furanose moiety closely related to similar structures found in hygromycin A (Figure 1). 5 The structural basis for both Hygromycin A and A201A antibiotics binding and inhibition to ribosomes have been recently showed by Polikanov et al 6 The similarities of A201A structure with puromycin and hygromycin A antibiotics strongly suggest that certain enzymes, and hence the corresponding genes in the A201A biosynthetic pathway, may be related to their counterparts in the puromycin and hygromycin A biosynthetic pathways. [7][8][9][10][11] Homologs of the ata open reading frames (ORFs) have indeed been found with for at least 14 ORFs of the hygromycin A biosynthetic cluster in S. hygroscopicus 9 and as we showed previously a set of five consecutive genes involved in the biosynthesis of the aminonucleoside moiety of A201A 12 and their deduced products (AtaP3, AtaP4, AtaP5, AtaP7 and AtaP10) are similar to their counterparts from the pur cluster of S. alboniger (Pur3, Pur4, Pur5, Pur7 and Pur10, respectively), genes implicated in the biosynthesis of the aminonucleoside moiety of puromycin.…”
Section: Introductionmentioning
confidence: 98%